Synthetic SARS-CoV-2 Spike-Based DNA Vaccine Elicits Robust and Long-Lasting Th1 Humoral and Cellular Immunity in Mice - Alamri, Sawsan S.; Alluhaybi, Khalid A.; Alhabbab, Rowa Y.; Basabrain, Mohammad; Algaissi, Abdullah; Almahboub, Sarah; Alfaleh, Mohamed A.; Abujamel, Turki S.; Abdulaal, Wesam H.; ElAssouli, M-Zaki; Alharbi, Rahaf H.; Hassanain, Mazen; et al. (Frontiers in Microbiology, 2021)
The ongoing global pandemic of coronavirus disease 2019 (COVID-19) calls for an urgent development of effective and safe prophylactic and therapeutic measures. The spike (S) glycoprotein of SARS-CoV-2 is a major immunogenic and protective protein and plays a crucial role in viral pathogenesis. In this study, we successfully constructed a synthetic codon-optimized DNA-based vaccine as a countermeasure against SARS-CoV-2, denoted VIU-1005. The design was based on a codon-optimized coding sequence of a consensus full-length S glycoprotein. The immunogenicity of the vaccine was tested in two mouse models (BALB/c and C57BL/6J). Th1-skewed systemic S-specific IgG antibodies and neutralizing antibodies (nAbs) were significantly induced in both models four weeks after three injections with 100 µg of the VIU-1005 vaccine via intramuscular needle injection but not intradermal or subcutaneous routes. Such immunization induced long-lasting IgG and memory T cell responses in mice that lasted for at least 6 months. Interestingly, using a needle-free system, we showed an enhanced immunogenicity of VIU-1005 in which lower or fewer doses were able to elicit significantly high levels of Th1-biased systemic S-specific immune responses, as demonstrated by the significant levels of binding IgG antibodies, nAbs and IFN-γ, TNF and IL-2 cytokine production from memory CD8+ and CD4+ T cells in BALB/c mice. Furthermore, compared to intradermal needle injection, which failed to induce any significant immune response, intradermal needle-free immunization elicited a robust Th1-biased humoral response similar to that observed with intramuscular immunization. Together, our results demonstrate that the synthetic VIU-1005 candidate DNA vaccine is highly immunogenic and capable of inducing long-lasting Th1-skewed humoral and cellular immunity in mice. Furthermore, we show that the use of a needle-free system could enhance the immunogenicity and minimize doses needed to induce protective immunity in mice, supporting further preclinical and clinical testing of this candidate vaccine.